Analysis of User Satisfaction Level of myIM3 Application Using TAM Method - Sayyidah 'Aisy Farikhah; Paramitha Nerisafitra (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2021)
User satisfaction is a critical thing in handling a business. The company must be capable to provide quality services for the products/services provided by them. MyIM3 application is an application developed by PT. Indosat Ooredoo Hutchison to check and purchase credit and data packages online, find promotions offered by Indosat Ooredoo Hutchison, etc. More than 10 million users have downloaded the myIM3 app on the PlayStore and AppStore. The number of features offered makes users often experience problems in accessing the application so it affects user satisfaction. This study aims to find a correlation between variables to determine the level of user satisfaction with myIM3 application. This study applied Technology Acceptance Model (TAM) method. The number of respondents obtained by using the calculation of Slovin's formula was 400. The technique of data collection used in this study was by distributing questionnaires to myIM3 users throughout the public with various criteria. The technique of data analysis used in this study was Structural Equation Model (SEM). From this study, the hypothesis that has the most significant influence is Attitude Toward Using to Behavioral Intention to Use, while other hypotheses which also have a significant influence are Perceived Ease of Use to Perceived Usefulness, Perceived Usefulness to attitude Toward Using, Perceived Ease of Use To attitude Toward Using, and Behavioral Intention to Use to User Satisfaction.